Media Baru dan Paham Radikalisme Pada Kalangan Remaja Di Kota Kendari Sulawesi Tenggara - La Ode Mansabdar Kanande; Yusyrifah Halid; Aldilal Aldilal; Aminudin Aminudin (The Journal of Society and Media, 2023)
This research aims to find out whether teenagers in Kendari City know the content of content that spreads radicalism on social media and how to respond to content that contains radicalism. Using descriptive qualitative methods, samples are taken by purposive sampling method. Data collection techniques are carried out with primary data & secondary data. Based on the findings, the researchers concluded: First, many teenagers in Kendari City do not have guidance or literacy regarding radicalism on social media, and few of them are teenagers who know accounts and content on social media that spread radicalism. Second, most teenagers in Kendari City choose to respond to accounts that are indicated to be radical on social media by reporting these accounts. Third, Few adolescents respond to choosing to keep seeing or consuming and allowing accounts that spread radical ideas to be vulnerable to being influenced or exposed to radicalism